Structural packaging : workbook. - Garrofé, Josep M., ....- (Barcelona : Index Book, 2005)
This is a complete book about packaging structures that includes about 150 original works each accompanied by a template, an explanation about the needs of the client, the designer's solution, information on the materials required, high-quality photographs of the finished work; plus a CD including all the works. The book is organised into three chapters: the first one features the easiest, cheapest and fastest works and the third the most difficult, expensive and complex.
Keywords: Verpakkingen